Evaluation of processing tomato cultivars for susceptibility to Fusarium stem rot and decline, 2024 - Brenna Aegerter; Patricia Lazicki; Cassandra Swett (Plant Health Progress, 2026)
Fusarium stem rot and decline (FRD), caused by two pathogens in the Fusarium solani complex (F. martii and F. noneumartii), impacts processing tomato production in California. It causes a premature vine decline which exposes fruits to sunburn and subsequent damage from fruit rot pathogens. This report evaluates yield performance of 24 commercial cultivars in a naturally infested commercial production field near Stockton, CA in 2024.